2001
DOI: 10.1128/jvi.75.20.9808-9818.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cellular COPII Proteins Are Involved in Production of the Vesicles That Form the Poliovirus Replication Complex

Abstract: Poliovirus (PV) replicates its genome in association with membranous vesicles in the cytoplasm of infected cells. To elucidate the origin and mode of formation of PV vesicles, immunofluorescence labeling with antibodies against the viral vesicle marker proteins 2B and 2BC, as well as cellular markers of the endoplasmic reticulum (ER), anterograde transport vesicles, and the Golgi complex, was performed in BT7-H cells. Optical sections obtained by confocal laser scanning microscopy were subjected to a deconvolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
208
4
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(221 citation statements)
references
References 87 publications
8
208
4
1
Order By: Relevance
“…Perinuclear collections of proliferative vesicles, indicative of sites of virus replication, were seen in some apoptotic cells (Fig. 1C, cell c) (36). Thus, both TUNEL and electron microscopic analyses indicated that M1-D cells undergo apoptosis as a result of BeAn virus infection.…”
Section: Temporal Kinetics Of Apoptosis In Bean Virus-infected M1-d Cmentioning
confidence: 85%
“…Perinuclear collections of proliferative vesicles, indicative of sites of virus replication, were seen in some apoptotic cells (Fig. 1C, cell c) (36). Thus, both TUNEL and electron microscopic analyses indicated that M1-D cells undergo apoptosis as a result of BeAn virus infection.…”
Section: Temporal Kinetics Of Apoptosis In Bean Virus-infected M1-d Cmentioning
confidence: 85%
“…These structures are derived sequentially from membranes of different cellular organelles. At early times following infection, PV-induced vesicles are probably formed in the ER (3,5,37), whereas at later times, membranes from other cellular organelles, including lysosomes and the Golgi apparatus, may also contribute to vesicle formation (4,5). RTN3 is an ER-associated protein, and its reduced expression in knockdown cells may affect the budding of replication complex vesicles manufactured from the ER compartment membrane (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Vesicular structures generated in picornavirus-infected cells appear to serve as compartments where synthesis of viral RNA takes place. These structures are derived from membranes of different cellular organelles involved in secretory pathways, primarily endoplasmic reticulum (ER) but also the Golgi complex and possibly others (2)(3)(4)(5). These membrane rearrangements are clearly triggered by the viral preprotein 2BC and its mature polypeptide 2C (6 -8).…”
mentioning
confidence: 99%
“…Since the Golgi plays a key role in the processing of viral envelope glycoproteins, and successful infection depends on the transport of newly synthesized viral proteins from the endoplasmic reticulum (ER) to the Golgi [7], abrogation of Golgi function during infection would be incompatible with virus replication. During the process of viral protein transport from the ER to Golgi and other vesicular transport, several Golgi and vesicular proteins, including COPs and Rabs, associate with viral proteins to facilitate their trafficking [26,38].…”
Section: Introductionmentioning
confidence: 99%